Unveiling the Correlation and Predictive Contribution of Digital Literacy and Critical Thinking to EFL Students’ Research Competence - Aisya, Firdha Rikhadatul; Mufidah, Nida (Proceeding International Conference on Education, 2025)
This study aims to identify the levels of digital literacy, critical thinking skills, and research competence among EFL students, and to examine the correlation and predictive contribution of the two independent variables to students’ research competence. Employing a quantitative approach with a correlational design, data were collected through multiple-choice tests administered to 66 eighth-semester students of the English Education Department at UIN Antasari Banjarmasin, all of whom had taken research-related courses and were conducting or had completed their undergraduate thesis. Descriptive statistics indicated that students demonstrated relatively high levels across all three variables: digital literacy (M = 79.00, SD = 8.35), critical thinking skills (M = 83.47, SD = 7.15), and research competence (M = 76.74, SD = 6.12). The results of multiple linear regression analysis revealed a strong and statistically significant correlation between digital literacy and critical thinking skills toward students’ research competence (R = 0.897, R² = 0.804). The regression coefficients showed that both variables positively contributed to the prediction of research competence, with critical thinking skills (B = 0.521) contributing slightly more than digital literacy (B = 0.463). These findings underscore the pivotal role of critical thinking and digital literacy in enhancing students’ research competence within the EFL context, and highlight the importance of integrating these skills more deeply into English language education and academic research training.